Rose's strategy of preventive medicine the complete original text - Rose, G. A. (Geoffrey Arthur); Rose, G. A. (Geoffrey Arthur). (Oxford : Oxford University Press, 2008)
Aimed at medical students and those who work in the health service, this book explores the options for the prevention of common diseases. It looks at the roots of such diseases through lifestyles, social factors and the environment.
Previous ed.: published as The strategy of preventive medicine. 2002.
Description based on print version record.
Includes index.
Keywords: Medicine, Preventive